Creation of the Femina Jury (1904): Coalition of Women Authors for the Right of Entry into the Republic of Letters - Ducas, Sylvie (Thélème. Revista Complutense de Estudios Franceses, 2026)
This study examines the origins of the Femina jury and its conflict with the Académie Goncourt over the dominance of women writers in the French literary scene at the beginning of the 20th century. This female uprising was not strictly speaking a feminist gesture, but it did raise the issue of women being excluded from the inner circles of literary recognition and deprived of authority in the field of literature. Above all, it will be shown that the media age and the publishing revolution were powerful allies in making female authors more visible at the beginning of the century.